The Effectiveness of Seed Biopriming with Mycorrhiza Fungi as an Effort to Improve the Quality of Germination and Curly Chili Production (Capsicum annum) - Meo, Monika Moi; Bao, Antonia P.; Demu, Melkior (Jurnal Biologi Tropis, 2024)
The biopriming technique is an alternative method to replace synthetic fungicides on chili seeds by applying a biological agent in the form of mycorrhizal fungi at the early seedling stage. Biological seed treatment can provide plant protection throughout its entire life cycle. This research aims to determine the chili varieties that provide the best growth and production response using the biopriming technique, the duration of seed soaking in the biopriming technique with mycorrhizae affecting the viability of chili seeds, and the interaction between the seed biopriming technique and curly chili varieties. The method used was experimental with a factorial design consisting of two factors: curly chili varieties (Tangguh F1 and MB-333 F1) and the duration of chili seed soaking (0, 24, 48, and 72 hours). The research results showed that the Tangguh F1 chili variety seeds with a 24-hour soaking treatment produced seeds with the most optimal germination rate, uniformity of growth, vigor index, plant height, number of leaves, flowering age, fruit length per plant, fruit diameter, and fruit weight per plant compared to all other treatments. The results of the variance analysis and significant difference test at the 5% significance level indicated that there were significant differences in germination rate, uniformity of growth, vigor index, plant height, number of leaves, flowering age, fruit length per plant, fruit diameter, and fruit weight per plant produced by the curly chili seeds given different soaking durations and chili varieties.